PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA AL RIFA’IE KELAS XI IIS GONDANGLEGI MALANG - Rochmatul Jalilah; Abdul Jalil; Kukuh Santoso (VICRATINA, 2021)
The role of the theacher in Islamic religious education at Al-Rifa’ie High School in education as a subject in the learning process at school. Islamic religious education teachers who are directly involved in the educational process at Al-Rifa’ie High School play an important role in the whole teaching and learning process to achieve educational goals, for that Islamic religious education teachers must be experts in order to carry out their duties and responsibilities properly including in Islamic religious education and morally Islamic religious education teachers are required to be able to direct their students to behave in accordance with the norms and ethics that apply in community life. The purpose of this study is to find out how the teacher’s role in increasing student interest in Islamic education subjects at SMA Al-Rifa’ie Class XI IIS Gondanglegi Malang. The researcher conducted this research using a qualitative research method with the type of case study on the entire teacher council which became the main role in increasing student interest in learning in Islamic religious education subjects at Al-Rifa’ie Gondanglegi High School Malang. Data analysis was carried out by condensing data, presenting data, drawing conclusions, and drawing conclusions. The results of the study, namely the role of teachers in increasing student interest in Islamic education subjects at Al-Rifa’ie High School Class XI IIS Gondanglegi Malang have the task of making students as IMTAQ humans, intellectuals, and have good morals. So that the task of religious teachers is not only to teach knowledge/lessons but how to make the knowledge they can be able to operate (practice) in everyday life.